Agenesis of the Internal Carotid Artery with Transcavernous Anastomosis Associated with Anterior Communicating Artery Aneurysms - Kumagai, Kosuke (Asian J Neurosurg, 2017)
Agenesis of the internal carotid artery (ICA) is a rare congenital anomaly. Recently, several cases of ICA agenesis have been associated with cerebral aneurysms. We present the seventh case of ICA agenesis with transcavernous anastomosis associated with cerebral aneurysms. A 47-year-old man presented with transient numbness of his left hand. Magnetic resonance angiography indicated the presence of anterior communicating artery (ACoA) aneurysms. Digital subtraction angiography revealed two ACoA aneurysms, absence of the left ICA, and an anomalous collateral vessel connecting the cavernous portions of both internal carotid arteries, which was considered to be a transcavernous anastomosis. Head bone window computed tomography with contrast medium revealed the absence of the petrous carotid canal on the left suggesting the diagnosis of left ICA agenesis. The ACoA aneurysms were clipped successfully, and the postoperative course was uneventful.